2020
DOI: 10.5114/aoms.2019.87938
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-610 acts as a tumour suppressor to depress the cisplatin resistance in hepatocellular carcinoma through targeted silencing of hepatoma-derived growth factor

Abstract: Introduction: Hepatic malignancy is one of the most common malignant neoplasms around the globe, and hepatocellular carcinoma (HCC) is the most common type. In this study, the roles and mechanisms of MiRNA-610 in the chemo resistance of HCC will be discussed. Material and methods: The expression of MiRNA-610 and hepatoma-derived growth factor (HDGF) in HCC tissues and cell line was detected by quantitative real-time PCR. The proliferation and chemo resistance were analysed by MTT assay. Flow cytometry was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…HBV infection is considered as a central reason for hepatocarcinogenesis. It is well known that host miRNAs are implicated in virus infection and replication [7,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV infection is considered as a central reason for hepatocarcinogenesis. It is well known that host miRNAs are implicated in virus infection and replication [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been demonstrated to be involved in kinds of physiological or pathological changes in human diseases [7]. Convincing evidence shows the association between host miRNAs and virus infection [8].…”
Section: Introductionmentioning
confidence: 99%
“…This sheds light on how miR-9 regulates HCC chemosensitivity and provides a potential target for enhancing the effectiveness of HCC chemotherapy [ 79 ]. Apart from its role as a tumor suppressor in HCC, miR-610 also affects the resistance of HCC cells to cisplatin by specifically silencing the HDGF gene [ 80 ]. Conversely, the targeting of FASLG by miR-21-5p decreased the sensitivity of HCC to cisplatin treatment [ 81 ].…”
Section: Mirnas and Systemic Treatment Resistancementioning
confidence: 99%
“…For example, Wuerkenbieke et al demonstrated that miRNA-150 downregulation contributed to the pertuzumab resistance in ovarian cancer via activating PI3K-Akt pathway 6 . Recently, Xu et al found that miRNA-610 could affect chemoresistance to DDP in hepatocellular carcinoma through targeted silencing of the HDGF gene 7 . Moreover, miRNA-375-3p could enhance 5-fluorouracil chemosensitivity in colorectal cancer by targeting thymidylate synthase 8 .…”
Section: Introductionmentioning
confidence: 99%